Dust, Cigarette Smoke, and Cold Air are the Main Risk Factors for Asthma Attacks - Agustina, Wiwik (Jurnal Respirologi Indonesia, 2024)
Background: The prevalence of asthma has increased worldwide over the past few decades, with an estimated incidence reaching 400 million people by 2025. By the end of 2020, the prevalence of asthma in Indonesia was 4.5% of the total population, exceeding 12 million individuals.Methods: This study aimed to analyze the most frequent risk factors for asthma attacks. A correlative descriptive design was employed, with a population consisting of all asthma patients. The sample was selected using purposive sampling, resulting in 30 respondents. This research was conducted in Malang and included respondents with a history of asthma who were not hospitalized.Results: Logistic regression analysis revealed that 72% of asthma recurrences were attributed to dust, cigarette smoke, cold air, family/hereditary history of disease, obesity, pollen, animal dander, seafood, eggs/nuts, fungi, and cow's milk. The remaining 28% were linked to other risk factors, including pregnancy, stress, excessive emotions, physical fatigue, weather changes, and more. The three primary risk factors for asthma attacks were dust (87%), cigarette smoke (83%), and cold air (73%).Conclusion: Asthma recurrence is primarily caused by hypersensitivity, with allergens triggering elevated IgE levels, leading to bronchoconstriction and subsequent asthma attacks. The findings of this study identified dust, cigarette smoke, and cold air as the main risk factors for asthma recurrence. Asthma patients need to recognize their allergens to facilitate preventive measures and reduce the likelihood of asthma attacks.